Analysis of Delays to Surgery for Cervical Spinal Cord Injuries. Issue 13 (1st July 2015) - Samuel, Andre M.; Bohl, Daniel D.; Basques, Bryce A.; Diaz-Collado, Pablo J.; Lukasiewicz, Adam M.; Webb, Matthew L.; Grauer, Jonathan N.
<x xml:space="preserve">Abstract</x> Study Design. A retrospective study of surgically treated patients with cervical spinal cord injury (SCI) from the National Trauma Data Bank Research Data Set. Objective. To determine how time to surgery differs between SCI subtypes, where delays before surgery occur, and what factors are associated with delays. Summary of Background Data. Studies have shown that patients with cervical SCI undergoing surgery within 24 hours after injury have superior neurological outcomes to patients undergoing later surgery, with most evidence coming from the incomplete SCI subpopulation. Methods. Surgically treated patients with cervical SCI from 2011 and 2012 were identified in National Trauma Data Bank Research Data Set and divided into subpopulations of complete, central, and other incomplete SCIs. Relationships between surgical timing and patient and injury characteristics were analyzed using multivariate regression. Results. A total of 2636 patients with cervical SCI were identified: 803 with complete SCI, 950 with incomplete SCI, and 883 with central SCI. The average time to surgery was 51.1 hours for patients with complete SCI, 55.3 hours for patients with incomplete SCI, and 83.1 hours for patients with central SCI. Only 44% of patients with SCI underwent surgery within the first 24 hours after injury, including only 49% of patients with incomplete SCI. The vast majority of time between injury and surgery was after admission, rather than in the emergency department or in the field. Upper cervical SCIs and greater Charlson Comorbidity Index were associated with later surgery in all 3 SCI subpopulations. Conclusion. The majority of patients with SCI do not undergo surgery within the first 24 hours after injury, and the majority of delays occur after inpatient admission. Factors associated with these delays highlight areas of focus for expediting care in these patient populations. Level of Evidence: 4